(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2017)
The concept of political freedom is one of the fundamental keys of Italian Civic Humanism. Baron, Skinner, Pocock, Hankins and other scholars have examined the meaning of political freedom in this turbulent period of Italian history. This article analyzes, from critical texts, the historical process by which freedom loses its political connection with the republican urban way of life and takes refuge in an idle, cortly and contemplative life. Our article studies the concept of freedom in relation to other concepts as virtue, republic, active life, leisure and contemplation, and the Platonic and Aristotelian influences.